UMKM Sebagai Pilar Penghasilan Masyarakat di Kota Medan - Aflah Muhajir; Robbani Hafidz Lubis; Edo Adrio; Fandi Ahmad Zain (STIKes Ibnu Sina Ajibarang, 2025)
Micro, Small and Medium Enterprises (MSMEs) have an important role in the economy of Medan City, making a major contribution to job creation and increasing people’s income. This research aims to examine the role of MSMEs in economic development at the local level, the challenges they face, and the opportunities available, with a focus on how MSMEs in Medan adapt to the rapid digital technology advancements. Based on the theories of economic growth, sustainable development, and financial access, the findings indicate that MSMEs in Medan not only contribute to the Regional Gross Domestic Product (PDRB) and employment absorption but also strengthen the stability of the city's economy. While MSMEs have significant opportunities, they face challenges such as rising prices and the need to adopt digital technology for marketing their products. To support the growth of MSMEs, several policy recommendations include improving access to finance, developing infrastructure, enhancing skills training, and facilitating market access through digital platforms. Overall, MSMEs in Medan are a key pillar of the local economy, with growth potential that continues to expand as they adapt to technology and receive appropriate government support.